2020
DOI: 10.3390/microorganisms8091377
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in Soils and Endosphere of Solanum tuberosum L. and their Response to Long-Term Fertilization

Abstract: An understanding of how fertilization influences endophytes is crucial for sustainable agriculture, since the manipulation of the plant microbiome could affect plant fitness and productivity. This study was focused on the response of microbial communities in the soil and tubers to the regular application of manure (MF; 330 kg N/ha), sewage sludge (SF; 330 and SF3x; 990 kg N/ha), and chemical fertilizer (NPK; 330-90-300 kg N-P-K/ha). Unfertilized soil was used as a control (CF), and the experiment was set up at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
0
10
0
1
Order By: Relevance
“…This study is a follow up to our previous work in which we described the response of endophytic microbial communities to the long-term fertilization of agricultural soils [29]. Since the community structure was significantly altered, in this study we focused on the metabolic processes happening in some of these fertilized soils.…”
Section: Introductionmentioning
confidence: 96%
“…This study is a follow up to our previous work in which we described the response of endophytic microbial communities to the long-term fertilization of agricultural soils [29]. Since the community structure was significantly altered, in this study we focused on the metabolic processes happening in some of these fertilized soils.…”
Section: Introductionmentioning
confidence: 96%
“…The DNA library for the ITS region was prepared by using specific primers and two-step PCR. The forward primer 5.8S_Fun 5-AACTTTYRRCAAYGGATCWCT-3 and reverse primer ITS4_Fun 5-AGCCTCCGCTTATTGATATGCTTAART-3 [17] were used for amplification of the ITS-2 region (all Sigma-Aldrich, St. Louis, MO, USA). The master mix content and temperature programs were adopted from a study by Kracmarova et al [17] with a few modifications.…”
Section: Dna Library Preparing and Sequencingmentioning
confidence: 99%
“…The forward primer 5.8S_Fun 5-AACTTTYRRCAAYGGATCWCT-3 and reverse primer ITS4_Fun 5-AGCCTCCGCTTATTGATATGCTTAART-3 [17] were used for amplification of the ITS-2 region (all Sigma-Aldrich, St. Louis, MO, USA). The master mix content and temperature programs were adopted from a study by Kracmarova et al [17] with a few modifications. Briefly, the first PCR reaction mix contained nuclease-free water, 1 µM of each of the appropriate primers, 0.02 U/µL of KAPA HiFi HotStart ReadyMix (KAPA Biosystems, Wilmington, MA, USA), and 2 µL of template in a total reaction volume of 15 µL.…”
Section: Dna Library Preparing and Sequencingmentioning
confidence: 99%
“…Our previous studies have shown how long-term fertilization influences soil enzymatic activity [ 38 ] and endophytic communities in potatoes [ 39 ]. This study focused on the effects of long-term crop rotations, and organic and chemical fertilizer application on soil bacterial and fungal communities in various soil types.…”
Section: Introductionmentioning
confidence: 99%